Quality of Life after Liver Transplantation. (1st April 1990) - Grant, David; Evans, David; Hearn, Margaret; Duff, John; Ghent, Cameron; Wall, William
Abstract : The results of liver transplantation are now well established in terms of graft and patient survival, but there is surprisingly little data on the quality of life attained. The authors mailed questionnaires to 32 consecutive adult liver recipients to assess their quality of life. Thirty-one patients (14 males, 17 females) with a mean age of 37 years (range 16 to 55), responded (97%). The mean time since transplantation was 19 months (range three to 50). Eighty percent of the respondents functioned at normal or near normal levels as measured by the Karnofsky Performance Index. Sixty-five per cent (20 patients) indicated they were currently able to live and function as they did before they became ill with liver disease. The respondents' scores were similar to normative scores on all of the following measures: life satisfaction, well being, and general affect (Campbell); and material well being, personal growth, marital relations, family relations and friendships (Evans). It is concluded that liver transplantation restores physical, mental and social well being in most patients with endstage liver disease.